Sketchy, Doubtful, Incomplete Jottings - Goethe, Johann Wolfgang von, 1749-1832 (London Penguin Classics, 2015)
Offers a selection of the maxims and reflections from one of Germany's greatest ever thinkers.
Keywords: Goethe, Johann Wolfgang von, 1749-1832 -- English